Deformation and seismicity near Sabancaya volcano, southern Peru, from 2002 to 2015 - Jay, Jennifer A. (2015)
We use interferometric synthetic aperture radar (InSAR) and local seismic data to investigate the cause of earthquake sequences near Sabancaya volcano in southern Peru from 2002 to 2014, with a particular focus on events leading up to the August 2014 phreatic eruption. InSAR‐observed deformation associated with earthquake swarms in late 2002, February 2013, and July 2013 is modeled by fault slip, with no need for magmatic sources to explain the deformation. The majority of the seismicity is an expression of the regional tectonic system, which is characterized by E‐W trending normal faults, but a link to the magmatic system is possible. The Mw 5.9 earthquake on 17 July 2013 occurred on a previously unmapped normal fault that continued to deform in the months following the earthquake. An increase in long period and hybrid seismicity and changes in fumarolic emissions in 2013–2014 culminating in the August 2014 eruption indicates the involvement of both tectonic and magmatic systems.